Classical framework sources and the representation of Islamic sciences - Yaacob, Solehah@Nik Najah Fadilah (2017)
Muslim World has been upholding the Tawhidic concept of Ubudiyyah with a massive accumulation of knowledge over the entire period which has spurred the rise of the great Islamic civilization. In presenting the concepts, Islamic sciences have been categorized the directions of its various aspects: theoretical as well as its practical application have been indicated. However, without meticulous and appropriate division of sources in Islamic sciences the combination of the theory and practical has failed to bring about the desired results. The Islamic sciences as presented currently do not commensurate with its magnitude, depth and brilliance as can be unveiled from the universe of Islamic Knowledge from a multitude of known sources in the Muslim World and elsewhere. The gigantic sources in Islamic sciences are books, film, journals, manuscripts and etc. need to be rearranged accordingly based on current requirement through re-paraphrasing the record or data collection. The paper focuses on revisiting knowledge of sources in Islamic sciences using descriptive and analytic approaches to highlight major issues and reasons for the overshadowing of Islamic sciences resulting in diminishing its real worth as the world’s pioneer in the knowledge in science.